If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 3y = -1 Solving 2 + 3y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3y = -1 + -2 Combine like terms: 2 + -2 = 0 0 + 3y = -1 + -2 3y = -1 + -2 Combine like terms: -1 + -2 = -3 3y = -3 Divide each side by '3'. y = -1 Simplifying y = -1
| 6a+(a+4)=(6a+a)+4 | | -3(x+9)=-45 | | m+5m+11=47 | | -2y+10=-3(2y+2) | | (7x+4)(2x^2-17x-9)= | | 0=-1.5a+3 | | -(7x-2)= | | -2(7w+6)=-14w+4 | | x+(x+25)+(3x)=435 | | -2(2+x)=-2x+1 | | -6x^2+15x=-7x-21 | | 48+8x=10x-6 | | n(n-1)(n-2)=0 | | 2x^2-7x+111=0 | | 3x^2-8x-11= | | -14a+6=12a-20 | | 5g-2g=45-2g | | A(b-6)= | | 4x^3+28x^2-120x=0 | | 3(x-2)+6=38.85 | | 5y-5=-2y+2 | | -2(3x-4)+12=28 | | 1.9+9.3=n+54.7 | | 0.45= | | 2(5x+9)=78 | | 3(x-1)=x+5 | | 9-4(2w+1)=7w-4(7+w) | | 3x+7+11x+1=180 | | 6x^3-11x^2-19x-6= | | 1.5a=0.4a | | 0=1-(20t+1) | | 6(5a+3b-2b)= |